Gambaran Pengetahuan, Sikap, dan Tindakan Masyarakat dalam Mematuhi Protokol Kesehatan Setelah Menerima Vaksinasi COVID-19 di Dusun Gubug Tahun 2022 - Monica Sonya Novenda; Indrayanti (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
The government is running a COVID-19 vaccination program to protect against the dangers of COVID-19, but the general public believes that once vaccinated against COVID-19, there is no need to follow health protocols because it is already safe. People must continue to comply with health protocols after receiving the Covid-19 vaccination because there is still a possibility of getting Covid-19 with mild or no symptoms. The aim of the study was to describe the knowledge, attitudes, and actions of the community in complying with health protocols after receiving the Covid-19 vaccination in Gubug Argosari Sedayu Bantul Hamlet in 2022. This study used a quantitative descriptive method and statistical analysis using univariate analysis. The research instrument was a questionnaire with 30 questions. Sampling with a simple random sampling technique yielded as many as 95 respondents. The results showed that 83 people (87.4%) had a good category of community knowledge, 78 people (82.1%) had a good attitude, and 59 respondents (62.1%) had an adequate category of action in complying with health protocols after receiving the Covid-19 vaccination. In conclusion, the people of Dusun Gubug have good category knowledge and attitudes as well as sufficient category actions in complying with health protocols after receiving the Covid-19 vaccination in 2022.